Systemic inflammatory indices and the risk of depression in individuals with sleep difficulties: A cohort study based on NHANES 2005–2020 - Ruolin Zhu; Lu Wang; Xingqi Wu; Kai Wang (Comprehensive Psychoneuroendocrinology)
Sleep difficulties are common and often precede depressive disorders. We aimed to explore the associations between systemic inflammatory markers and depression risk in individuals with difficulty sleeping. We utilized data from the National Health and Nutrition Examination Survey (NHANES, 2005–2020), encompassing 7916 participants who reported having difficulty sleeping. The systemic inflammation response index (SIRI) and neutrophil‒platelet ratio (NPR) were calculated using peripheral blood cell counts. Odds ratios (ORs) and 95 % confidence intervals (CIs) of the SIRI/NPR for depression risk were calculated via logistic regression models. Restricted cubic spline (RCS) analysis was used to examine the dose‒response relationships between these indices and depression risk, whereas receiver-operating characteristic (ROC) analysis was used to evaluate their prognostic accuracy for depression risk. Participants in the highest SIRI and NPR quartile groups had significantly greater depression risk than those in the lowest quartile group did (OR (SIRI): 1.50, 95 % CI = 1.10–2.04; OR (NPR): 1.49, 95 % CI = 1.04–2.13). Subgroup analyses revealed consistent associations across different demographics and clinical subgroups. RCS analyses revealed a nonlinear association between depression risk and the SIRI (J-shaped, P nonlinearity <0.001) but not the NPR (P nonlinearity >0.05). ROC analysis revealed moderate discriminative ability for both the SIRI (AUC = 0.66, 95 % CI = 0.64–0.68) and the NPR (AUC = 0.65, 95 % CI = 0.63–0.67) in predicting depression among individuals with difficulty sleeping. These findings suggest that the SIRI and NPR are independently associated with increased depression risk among individuals with difficulty sleeping.